The Role of Skin Dysbiosis and Quorum Sensing in Atopic Dermatitis - Hiroki Okamoto; Shuo Li; Yuumi Nakamura (JID Innovations)
The skin microbiome plays a crucial role in the pathogenesis of atopic dermatitis (AD), a chronic inflammatory skin disorder strongly associated with microbial dysbiosis, particularly Staphylococcus aureus colonization. However, the mechanisms linking S aureus to AD remain insufficiently understood. This review explores the impact of the quorum-sensing (QS) system, particularly the accessory gene regulator Agr, in AD development and progression. By examining key microbial–host interactions, we provide insights into how QS influences skin inflammation and dysbiosis. Furthermore, we discuss the potential of microbiome-targeted therapeutic strategies to mitigate or prevent AD, highlighting their implications for future research and clinical applications.